Theoretical review of the treatment of pigmented lesions in Asian skin - Kono, Taro (Laser Ther, 2016)
Asian skin has a higher epidermal melanin content, making it more likely to develop adverse pigmentary reactions following laser surgery. The nanosecond lasers are the gold standard for the treatment of pigmented lesions, but the risk of complications, such as post-inflammatory hyperpigmentation, is increased in dark-skinned patients. Intense Pulsed Light (IPL) or long-pulsed lasers are available for treating superficial pigmented lesions, and fewer complications are seen when using these devices compared to the nanosecond lasers. Nanosecond lasers are essential in the treatment of dermal melanosis. Recently, picosecond lasers have been investigated. Picosecond lasers will also play an important role in the treatment of pigmented lesions.